Wastewater-based epidemiology for monitoring enteric viruses: a case study in Valladolid, Spain (2020–2021) - Casado-Martín, Lorena; Hernández, Marta; Yeramian, Nadine; González-Peña, Maria Jose; Eiros, José M.; Rodríguez-Lázaro, David (Frontiers in Microbiology, 2025)
Wastewater-based epidemiology (WBE) has been employed for decades and gained renewed significance with the emergence of SARS-CoV-2 at the end of 2019. The incidence of foodborne outbreaks has increased in recent decades, particularly those causing gastroenteritis and diarrhea, which are often of viral origin. However, because many enteric viruses are difficult or uncommon to diagnose, their frequency is often underestimated in comparison to bacterial diseases. WBE provides a valuable alternative for monitoring the presence and evolution of different enteric viruses within a population. This study monitored the major enteric viruses that are potential hazards to public health, including human noroviruses genogroup I and II (NoV GI and GII), human astroviruses (HastV), rotaviruses (RV), and hepatitis A (HAV) and E (HEV) viruses. Viral concentration was performed using an aluminum-based precipitation method, followed by RNA extraction and RT-qPCR quantification. Surveillance was conducted during the COVID-19 pandemics, from October 2020 to October 2021 in Valladolid, Spain, and its surrounding areas. The results showed that both genogroups of noroviruses exhibited the highest normalized concentration levels (5.42 ± 0.08 and 5.44 ± 0.09 Log gc/L, respectively). They were followed by RV (4.41 ± 0.07 Log gc/L) and HastV (6.00 ± 0.11 Log gc/L). Positivity rates were also greater for noroviruses, especially NoVGII (62% and 83.30%, respectively). However, in this case, RV presented a slightly higher positivity rate (46.70%) than HastV (41.30%). Meanwhile, HEV was detected only once (0.67% positivity), and HAV was absent throughout the study period. Additionally, lower concentration levels of the monitored pathogens were detected, compared to later periods, likely because of public health measures implemented during the COVID-19 pandemic. In conclusion, these findings highlight the potential of WBE for the early detection and monitoring of enteric virus outbreaks, particularly during public health crises.